The Effect of Compensation and Career Development on Turnover Intention With Job Satisfaction as A Mediating Variable and Employment Engagement as A Moderating Variable PT Nesia PAN Pacific KNIT - Sadewa, Bakti; Inggarwati, Komala (Dinasti Publisher, 2025)
This study aims to examine the impact of compensation, career development, and job satisfaction on turnover intention, with job satisfaction acting as a mediating variable. In addition, employment engagement is analyzed as a moderating variable to strengthen the effect of compensation and career development on turnover intention. The research was conducted using a quantitative approach with Structural Equation Modelling (SEM) to test the hypotheses. The sample consists of employees from various companies. The results indicate that compensation positively and significantly influences job satisfaction. Similarly, career development has a positive and significant effect on job satisfaction, supporting the hypotheses. However, compensation's influence on turnover intention was found to be insignificant, leading to the rejection of this hypothesis. In contrast, career development positively and significantly influences turnover intention. Job satisfaction was also found to mediate the effects of both compensation and career development on turnover intention. Additionally, employment engagement significantly moderates the relationship between career development and turnover intention, but its moderating effect on compensation was not significant. The findings of this study highlight the importance of fair compensation and career development programs in enhancing employee satisfaction and reducing turnover intention. Companies should prioritize these factors in their human resource strategies to foster higher employee retention rates.